Application Of Questioning Skills To Train Critical Thinking In Early Childhood - Wardhani, Wahju Dyah Laksmi; Misyana (Cita konsultindo, 2025)
This article aims to narrate the results of good practices in the application of questioning skills to train critical thinking skills carried out by students of the teacher profession program who are currently studying for teacher profession education at one of the universities in East Java. Learning designed with a project play approach with STEAM content is the basis for designing learning activities carried out for early childhood. This research is a type of qualitative research, with data collection techniques based on 3 cycle learning videos carried out by 2 students. One student carries out learning activities based on the 2013 Early Childhood Education Program curriculum and one student has implemented the Independent Curriculum. Data analysis is presented with an integrative narrative approach, namely integrating the results of observations of the experiences of one student with other students at the same stage. The results of the study show that teacher skills in asking questions can improve children's understanding of the STEAM concept more broadly and deeply.